Numerical Simulation Research on Crack Bifurcation Mechanism of Bidirectional Cumulative Tensile Blasting. (20th May 2020) - Guo, Pengfei; Ye, Kengkeng; Zhang, Xiaohu
Abstract : Shaped energy blasting has been widely used in the field of geotechnical engineering because of its good orientation and high energy utilization. However, the bifurcation of cracks in the direction of energy accumulation seriously affects the precracking effect in the direction of energy accumulation. In order to study the influence of the shaped energy angle on the crack propagation and bifurcation in the direction of energy accumulation, this paper used theoretical analysis and numerical simulation to study the influence of the energy angle on the crack propagation law in the energy-concentration direction. It was found that the energy release rate in the direction of energy accumulation after blasting was the main determinant of crack propagation and bifurcation in the direction of energy accumulation, and it decreased with the increase of the shaped energy angle. When the energy release rate in the direction of energy absorption exceeded a certain critical value, the stress intensity factor K at the crack tip would be affected by the impact load more than the bifurcation toughness K B, resulting in bifurcation of the crack in the direction of the energy. The SPH method was used to simulate and analyze the energy blasting of four different shaped energy angles. The results show that as the shaped energy angle increases when the shaped energy angle is greater than or equal to 35°, the cracks in the direction of energy accumulation after blasting are bifurcated, two cracks at the crack tip. When the shaped energy angle is less than 24°, only one horizontal crack is generated in the direction of shaped energy, which is in good agreement with the theoretical analysis. The research in this paper will provide a certain research basis for the design of the blasting device and the optimization of the blasting effect.